2020
DOI: 10.17843/rpmesp.2020.374.5838
|View full text |Cite
|
Sign up to set email alerts
|

Oferta y publicidad de alimentos y bebidas en instituciones educativas y entornos escolares de Lima Metropolitana. Un estudio exploratorio

Abstract: El objetivo del estudio fue describir la oferta y la publicidad de alimentos y bebidas en instituciones educativas y entornos escolares de 15 colegios públicos y privados de Lima en 2019. Se realizaron observaciones inopinadas y se registraron los alimentos ofrecidos, la presencia de advertencias publicitarias, octógonos y la publicidad en quioscos y cafeterías. A la hora de salida se observó la venta ambulatoria de alimentos. Todas las escuelas ofrecían productos ultraprocesados, el 73,3% vendía alimentos con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
0
14
0
3
Order By: Relevance
“…Studies reported a greater proximity of food outlets (especially grocery stores and fast-food restaurants) from high schools than preschools or elementary schools. The authors report that the flexibility of schedules, greater independence, and autonomy of high school students can decoy for the food market, in addition to the privileged location of schools on high-traffic roads, coinciding with the location of restaurants and supermarkets [ 2 , 13 , 26 , 32 , 35 , 39 , 50 , 64 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies reported a greater proximity of food outlets (especially grocery stores and fast-food restaurants) from high schools than preschools or elementary schools. The authors report that the flexibility of schedules, greater independence, and autonomy of high school students can decoy for the food market, in addition to the privileged location of schools on high-traffic roads, coinciding with the location of restaurants and supermarkets [ 2 , 13 , 26 , 32 , 35 , 39 , 50 , 64 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…A minority of authors chose to map the availability of food sold in the surroundings through subjective measures, including questionnaires applied to the school community ( n = 4) and direct observation by the authors themselves ( n = 2). Three studies identified food outlets through a questionnaire in which school administrators identified the presence of food outlets’ walkability [ 46 ] or a “seven to ten-minute walk from the school” [ 13 , 55 ]. Henriques et al [ 66 ] used an audit tool to record observations of the different types of food outlets found within 500 m of the school.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, even though the study found significant changes in some food categories and marketing strategies after the implementation of FOPL policy, the results show that most “high-in” products already used either marketing techniques or claims, and that it is increasing. So, it is important to inform and raise public awareness about how to evaluate the nutritional quality of a product, not only based on the content of nutrients of concern, which may be insufficient for some populations to identify healthy products ( 28 ), but also based on different traits such as ingredients, processing, and labeling. In Peru, the current public policies like the Law of Promotion of Healthy Eating ( 22 ), the Healthy Eating Guidelines ( 38 ) and the National Multisectoral Health Policy to 2030 ( 39 ) allow the implementation of other actions such as implementing communication-based or educational interventions for the clear interpretation of product healthfulness and informed decision-making regarding healthy food purchases.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we selected the eight categories of foods and beverages most consumed by children and adolescents ( 5 , 27 , 28 ; Supplementary Table 2 ):…”
Section: Methodsmentioning
confidence: 99%